Lexical restructuring in preliterate children: Evidence from novel measures of phonological representation. (1st September 2015) - AINSWORTH, STEPHANIE; WELBOURNE, STEPHEN; HESKETH, ANNE
ABSTRACT: There is substantial debate in the literature surrounding the development of children's phonological representations (PRs). Although infant studies have shown children's representations to contain fine phonetic detail, a consensus is yet to be reached about how and when phonemic categories emerge. This study used novel implicit PR measures with preschool children ( n = 38, aged 3 years, 6 months to 4 years, 6 months) to test predictions made by these competing accounts of PR development. The measures were designed to probe PR segmentation at the phoneme (rather than the phone) level without requiring an explicit awareness of phonemes. The results provide evidence in support of vocabulary driven restructuring, with PR segmentation found to be related to vocabulary when controlling for age.